Dukungan Manajemen Puncak terhadap Strategic Purchasing dalam Berkomunikasi dan Berkolaborasi dengan Supplier untuk Meningkatkan Kinerja Perusahaan - Zeplin Jiwa Husada Tarigan (Jurnal Manajemen dan Wirausaha, 2009)
The relationship between buyers and suppliers has received considerable attention in recent years. There are fourth major questions being discussed in this research, i.e. firstly, how to determine the support of the top management to influence strategic purchasing; secondly, how to determine the influence of strategic purchasing to good communication and collaboration with supplier; and thirdly, how to determine the influence of communication and collaboration to supplier involvement; and the last, how to increase enterprise performance by collaboration and supplier involvement. Based on previous research, it is found that top management support influenced to strategic purchasing and effect to communication and collaboration and affect to supplier involvement. Collaboration and supplier involvement have been to influence enterprise performance. According survey by questionnaires to 105 respondent and 98 completed questionnaires were returned. Two responses were considered incomplete and had to be discarded, and this left 96 valid responses. It is found, top management support as an organization don’t have influenced strategic purchasing, but strategic purchasing have impact to communication and collaboration to supplier involvement. Collaboration will bring significant contribution to increase performance, even without the supplier involvement.